TEACHING PATERN USED BY THE ENGLISH TEACHERS IN TEACHING AND LEARNING PROCESS - Septiani, Rika (Syntax Literate, 2017)
The research was carried out at SMA Negeri 1 and SMA Negeri 3 Kuningan from August 2014 to October 2014by using qualitative method in observational design. The respondents of this research were the English teachers of grade XII. The data analysis applied the descriptive data. The data were taken from the observation and interview. The observation held in the activity of the teaching and learning process, and the interview done to the English teachers after teaching and learning process. Descriptive analysis was applied to analyze by underlying words, word phrase and sentences, sharpening the early focus by continued observation and/or in depth interview The result of this research is the English teachers used the pattern of classroom English with several aspects; get thing done in the classroom, asking questions, beginning of lesson, end of lesson, textbook activity, games and songs, repetition and response, encouragement and confirmation, set phrase, text book activity, blackboard activity, repetition and response, progress in work. The aspect of asking question was the most patterns used by the English teachers in teaching and learning process. The main reason that the English teachers more use asking and question in the teaching and learning process were they want to stimulate the students to be an active one and to rich the effective of classroom teaching and learning activity.